Teacher Identity: The Case of Special Education Teachers. A Systematic Review of the Literature - Vergara-Rodríguez, Mauricio (2025)
Introduction. A literature review of the last ten years on the identity focuses of special education teachers due to the challenges of inclusive education and teacher training policies is presented. Addressing the teaching and professional identity of these subjects in different contexts allows us to identify the concepts, functions, and challenges currently faced by inclusive education, initial teacher training, and the integration of special educators into the educational system, considering as objectives to determine the theoretical and methodological constructions and research findings. Methodology. It was guided by PRISMA (2020) indications in three databases: WoS, Scopus, Eric, and Dialnet. From the 19 articles incorporated, qualitative emergent categories were identified and linked to the position and linkage of the concept of identity in the corpus. The first category synthesizes research that considers factors or variables that significantly impact how teachers construct and perceive their own identities. The second category identified identity as a direct theoretical perspective for understanding the subjects, their experiences, and their actions as teachers. Results. Identity has a sense of care, commitment, and connection with the other, invisibilized in their experience as professionals and in their training for inclusion processes, and, paradoxically, because of the tensions generated by a normalized educational system, educators maintain specific logics of reproduction of exclusion.